Meso-level processes of intellectual imperialism: the disruption of intellectual lineage formation in modern Japan and China by 'juniority effects'. - Chew, Matthew Ming-tak (Third World Quarterly, 2025)
The contemporary sociology of knowledge treats meso-level institutions of intellectual production as its primary investigative focus but seldom studies global intellectual inequalities. Decolonial and postcolonial studies of knowledge focus on global intellectual inequalities, but they seldom examine meso-level institutions. This study's research objective is to help bridge the research gap that results from these two fields' disconnection: meso-level processes of intellectual imperialism. It does so by analysing the disruption of intellectual lineage formation in non-Western contexts and theorising this disruption as a processual aspect of intellectual imperialism. It coins the shorthand term 'juniority effects' to describe these relational processes. It investigates data on the careers of the first two cohorts of prominent thinkers in Japan between the 1860s and the 1910s and in China between the 1880s and the 1920s. The data sources include a wide variety of primary historical materials and secondary studies. Based on illustrating how these thinkers experienced and confronted reputational disruptions, it illustrates that juniority effects existed and seriously obstructed local intellectual lineages.